Effectiveness of Vestibular Rehabilitation Exercises On Dizziness-Handicap among Patients with Vertigo Attending ENT OPD at A Selected Hospital - Malathi, Thota; Seethalakshmi, A.; Akila, P. (Journal of Health and Allied Sciences NU, 2016)
Objective: The current research aims to identify the effect of Vestibular rehabilitation exercises on the dizziness-handicap among patients with vertigo.Methods: The research design adopted is a pretest-posttest design. 30 patients with vertigo attending the ENT out Patient Department (OPD) who fulfilled the inclusion criteria were selected randomly by lottery method, 15 were assigned to the study and 15 to the control group respectively. Vestibular rehabilitation exercises which include eye, head, sitting, standing & st walking exercises were demonstrated to the study group patients on 1st consultation using a booklet for 20 minutes along with return demonstration. The patients were reinforced to perform the exercises twice daily for 7th days following which the posttest was carried out on the th 7 day. The control group received routine care.Results: The results showed that in the study group 86.7% had severe level of dizzinesshandicap during the pretest which was reduced after practicing vestibular rehabilitation to 13.3% during the posttest, whereas in the control group it was 66.7% and 73.3% who had severe level of dizziness-handicap during the pretest and the posttest respectively. The mean for dizziness handicap for the study group at pretest was 66.3±14.03 and at posttest it was 31.07 ±18.94. The control group showed that at pretest the mean was 61.33±15.24 and at posttest it was 63.87±22.35. This was found to be significant at p=0.0005.Conclusion: The study supported the hypothesis that vestibular rehabilitation exercises had an impact on the dizziness handicap.
Keywords: rehabilitation; dizziness-handicap; vertigo